2003
DOI: 10.1093/her/cyf044
|View full text |Cite
|
Sign up to set email alerts
|

Social participation and health in a community rich in stock of social capital

Abstract: In Finland, members of the Swedish-speaking minority, many of whom live in the province of Ostrobothnia, intermingle with the Finnish-speaking majority. Although the two language communities are quite similar to each other in most societal respects, including socioeconomic status, education and use of health services, significant disparities have been reported in the morbidity, disability and mortality between the Swedish-speaking minority and the Finnish-speaking majority. Since the population genetic, ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
3
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(129 citation statements)
references
References 29 publications
10
108
3
8
Order By: Relevance
“…For SPH status, in line with previous studies for the whole population (Bolin et al 2003;Hyyppä and Mäki 2003;Poortinga 2006a,b), we find the individual social relations variable positively associated with the probability of declaring good self-perceived health while the contextual social relations variable is not found statistically significant. Novel results regard chronic conditions and limitations in daily activities status.…”
Section: We Analyse New Data From An Income and Living Conditions Sursupporting
confidence: 91%
See 1 more Smart Citation
“…For SPH status, in line with previous studies for the whole population (Bolin et al 2003;Hyyppä and Mäki 2003;Poortinga 2006a,b), we find the individual social relations variable positively associated with the probability of declaring good self-perceived health while the contextual social relations variable is not found statistically significant. Novel results regard chronic conditions and limitations in daily activities status.…”
Section: We Analyse New Data From An Income and Living Conditions Sursupporting
confidence: 91%
“…In particular, being separated and/or divorced is negatively associated, respectively, with a 1.6 and 3.4 percent higher probability of declaring good perceived health (moving from fair perceived state). Previous empirical studies on whole population found similar evidence (Bolin et al 2003;Hyyppä and Mäki 2003;Iversen 2008). Moreover, having children aged 6-15 is negatively statistically correlated (at 10%) with SPH, too.…”
Section: Self-perceived Healthsupporting
confidence: 69%
“…Social capital refers to the quantity and quality of social relationships such as formal and informal social connections as well as norms of reciprocity and trust that exist in community [9]. Many recent studies have found that high levels of social capital are associated with better health [10,11].…”
Section: Primary Prevention For Long-term Carementioning
confidence: 99%
“…According to Lochner, Kawachi and Kennedy (1999) this collective approach implies that social capital is not an individual property. However, even if it has a collective feature, the effects can be evaluated at the individual level (Hyyppa & Maki, 2003). Rothstein and Stolle (2003) claim that social capital can be defined both at individual and collective level.…”
Section: Social Capitalmentioning
confidence: 99%